Effect of sugarcane cultivars infected with sugarcane yellow leaf virus (Scylv) on feeding behavior and biological performance of melanaphis sacchari (hemiptera: Aphididae) - Bertasello, Luiz Eduardo Tilhaqui [UNESP]; Carmo‐sousa, Michele; Prado Maluta, Nathalie K.; Rossini Pinto, Luciana [UNESP]; Spotti Lopes, João R.; Gonçalves, Marcos Cesar [UNESP] (MDPI, 2021)
Sugarcane yellow leaf virus (ScYLV), Polerovirus, Luteoviridae, is one of the main viruses that infect sugarcane worldwide. The virus is transmitted by the aphid Melanaphis sacchari in a persis-tent, circulative manner. To better understand the interactions between ScYLV, sugarcane geno-types and M. sacchari, we explored the effect of sugarcane cultivars on the feeding behavior and biological performance of the vector. The number of nymphs, adults, winged, total number of aphids and dead aphids was assayed, and an electrical penetration graph (EPG) was used to mon-itor the stylet activities. Multivariate analysis showed changes in the vector’s behavior and biology on cultivars, identifying specific groups of resistance. In the cultivar 7569, only 5.5% of the insects were able to stay longer on sustained phloem ingestion, while in the other seven cultivars these values varied from 20% to 60%. M. sacchari showed low phloem activities in cultivars 7569 and Bio266. Overall, cultivar 7569 showed the worst biological performance of aphids, with the insects presenting mechanical difficulties for feeding and a shorter duration of the phloem period, and thus being considered the most resistant. We conclude that ScYLV virus infection in different sugarcane cultivars induced specific changes in the host plant, modifying the behavior of its main vector, which may favor or impair virus transmission.
Keywords: Aphid performance; Electrical penetration graph; Plant virus resistance; Probing behavior; Saccharum spp